A brief survey on law and economics of contract law - Yusuf Sertaç Serter (Juridical Tribune, 2019)
Right to own property and freedom of contract are two fundamental rights for the good of society. That’s to say – together with property law – contract law is vital for a good functioning economy. Thus, contract is a solid instrument to increase social welfare. Accordingly, a brief description of economic analysis of contract law will be carried out in this essay. As such, the author of the essay attempts to find appropriate answers to certain major questions including the following: Why are contracts good from a societal point of view? What types of risks can arise in a contract? What is a fully specified contract and how will risks be allocated in a fully specified contract? Why is a particular risk allocation in contracts important for both society and contracting parties? What are the consequences of transaction costs for contract law? What is the economic purpose of codification of default rules?